The value of osteology in an historical context: a comparison of osteological and historical evidence for trauma in the late 18th- to early 19th century British Royal Navy - Boston, C (2014)
Trauma is arguably the most comparative and least ambiguous of palaeopathological lesions. As such, it is an ideal vehicle for exploring the respective contributions and differences between historical and osteological approaches to health in the past. A direct comparison between historical and osteological assemblages is often impossible due to the lack of comparable data, or complicated by the very different perceptions, motivations and pre-occupations of past writers and present researchers. Nevertheless, where genuine opportunities exist to compare and contrast the alternative strands of evidence, it may lead to a much richer and more nuanced understanding of the past. This study uses trauma in the late 18th- to early 19th century British Royal Navy (R.N.) to explore the differences between the two disciplines, and through this process to come to a deeper understanding of the physical effects of a maritime lifestyle on the health of late 18th- to early 19th century R.N. seamen and marines. The 18th- and early 19th century R.N. is one of the best documented institutions of its day, with a large corpus of records accessible in the National Archives in Kew. Recent archaeological excavations in the burial grounds of the three R.N. hospitals of the 18th century in Britain- the Royal Hospitals Haslar in Gosport, Stonehouse in Plymouth and Greenwich Hospital in South-East London- have made available over 300 skeletons of seamen and marines, who were treated but died in these institutions. This study explores the osteological evidence for fractures and joint trauma patterning in 300 of these skeletons. Eighteenth century accounts of the privations and dangers of sailing a fighting ship are well supported osteologically by the presence of 926 fractures and 14 joint dislocations. Osteological trauma patterning was compared with historical data collated from the Haslar and Plymouth Hospital musters (1792-1824) and Entry Books of Greenwich Hospital (1749-1765). The most probable aetiology of injuries was explored using insights from modern medical and forensic research, and 18th century sea surgeons' journals. Falls accounted for a very high proportion of injuries in both datasets, as did crush injuries, and to a much lesser extent, battle trauma. Extremely high rates of nasal fractures, Bennett's fractures of the first metacarpal, and anterior rib fractures in the skeletal assemblages strongly suggest very high rates of casual interpersonal violence. Interestingly, these injuries were very seldom recorded in either sea surgeon or hospital records, possibly due to seamen's fear of punishment for transgressing official naval regulations against fighting. Several unusual fractures (such as Shepherd's fractures of the talus, and third metacarpal avulsion fractures) and bony modifications (such as shallow and unstable hip and shoulder joints, os acromiale and Eagle's syndrome) appear to be the consequences of engaging in a maritime lifestyle, often beginning in childhood or adolescence. Trauma is arguably the most comparative and least ambiguous of palaeopathological lesions. As such, it is an ideal vehicle for exploring the respective contributions and differences between historical and osteological approaches to health in the past. A direct comparison between historical and osteological assemblages is often impossible due to the lack of comparable data, or complicated by the very different perceptions, motivations and pre-occupations of past writers and present researchers. Nevertheless, where genuine opportunities exist to compare and contrast the alternative strands of evidence, it may lead to a much richer and more nuanced understanding of the past. This study uses trauma in the late 18th- to early 19th century British Royal Navy (R.N.) to explore the differences between the two disciplines, and through this process to come to a deeper understanding of the physical effects of a maritime lifestyle on the health of late 18th- to early 19th century R.N. seamen and marines. The 18th- and early 19th century R.N. is one of the best documented institutions of its day, with a large corpus of records accessible in the National Archives in Kew. Recent archaeological excavations in the burial grounds of the three R.N. hospitals of the 18th century in Britain- the Royal Hospitals Haslar in Gosport, Stonehouse in Plymouth and Greenwich Hospital in South-East London- have made available over 300 skeletons of seamen and marines, who were treated but died in these institutions. This study explores the osteological evidence for fractures and joint trauma patterning in 300 of these skeletons. Eighteenth century accounts of the privations and dangers of sailing a fighting ship are well supported osteologically by the presence of 926 fractures and 14 joint dislocations. Osteological trauma patterning was compared with historical data collated from the Haslar and Plymouth Hospital musters (1792-1824) and Entry Books of Greenwich Hospital (1749-1765). The most probable aetiology of injuries was explored using insights from modern medical and forensic research, and 18th century sea surgeons’ journals. Falls accounted for a very high proportion of injuries in both datasets, as did crush injuries, and to a much lesser extent, battle trauma. Extremely high rates of nasal fractures, Bennett’s fractures of the first metacarpal, and anterior rib fractures in the skeletal assemblages strongly suggest very high rates of casual interpersonal violence. Interestingly, these injuries were very seldom recorded in either sea surgeon or hospital records, possibly due to seamen’s fear of punishment for transgressing official naval regulations against fighting. Several unusual fractures (such as Shepherd’s fractures of the talus, and third metacarpal avulsion fractures) and bony modifications (such as shallow and unstable hip and shoulder joints, os acromiale and Eagle’s syndrome) appear to be the consequences of engaging in a maritime lifestyle, often beginning in childhood or adolescence.